2011
DOI: 10.1021/es103934x
|View full text |Cite
|
Sign up to set email alerts
|

Species-Specific Differences and Structure−Activity Relationships in the Debromination of PBDE Congeners in Three Fish Species

Abstract: Previous studies have suggested that there may be species-specific differences in the metabolism of polybrominated diphenyl ethers (PBDEs) among different fish species. In this study, we investigated the in vitro hepatic metabolism of eleven individual PBDE congeners (tri-through decaBDEs) in three different fish species: rainbow trout (Oncorhynchus mykiss), common carp (Cyprinus carpio), and Chinook salmon (O. tschwatcha). In addition, we evaluated the influence of PBDE structural characteristics (i.e., bromi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

17
180
1
3

Year Published

2012
2012
2017
2017

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 198 publications
(201 citation statements)
references
References 27 publications
(121 reference statements)
17
180
1
3
Order By: Relevance
“…The significant depletion in 13 C for BDE-47 in common carp indicates that a large amount of BDE-47 was formed from metabolic debromination of more highly brominated congeners. The constant δ 13 C value for BDE-100 in common carp and in Penta-BDE indicated that BDE-100 was accumulated by common carp with or without undetectable biotransformation, which is in line with the results of laboratory exposure experiments (Roberts et al, 2011).…”
Section: Application To Laboratory-exposed Common Carpsupporting
confidence: 85%
“…The significant depletion in 13 C for BDE-47 in common carp indicates that a large amount of BDE-47 was formed from metabolic debromination of more highly brominated congeners. The constant δ 13 C value for BDE-100 in common carp and in Penta-BDE indicated that BDE-100 was accumulated by common carp with or without undetectable biotransformation, which is in line with the results of laboratory exposure experiments (Roberts et al, 2011).…”
Section: Application To Laboratory-exposed Common Carpsupporting
confidence: 85%
“…Although early embryonic development of red-eared sliders and snapping turtles is similar [42,43], species-specific differences are likely in enzymatic systems potentially responsible for differential capacities for debromination, as has been shown in fish exposed to BDE-99 [7,10]. Several studies of fish have shown debromination of BDE-99 to BDE-47 in carp, but other species such as Chinook salmon and rainbow trout demonstrate different reductive metabolite products and slower formation rates [6,7,9,10]. Deiodinase enzymes (DIs)-which are responsible for the removal of iodine atoms from thyroid hormones, resulting in activation or deactivation of the hormones-have been suggested as the primary enzymatic system for debromination of BDE-99 to BDE-47 in fish, particularly in carp [7,9,10].…”
Section: Discussionmentioning
confidence: 95%
“…McKernan et al [8] reported the presence of several PBDE congeners in the egg contents of several species of birds that had been injected with DE-71 but were not detected in the dosing solution or control eggs. Although early embryonic development of red-eared sliders and snapping turtles is similar [42,43], species-specific differences are likely in enzymatic systems potentially responsible for differential capacities for debromination, as has been shown in fish exposed to BDE-99 [7,10]. Several studies of fish have shown debromination of BDE-99 to BDE-47 in carp, but other species such as Chinook salmon and rainbow trout demonstrate different reductive metabolite products and slower formation rates [6,7,9,10].…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations